Characterization of the photosynthetic pathway of some tropical food yams (Dioscorea spp.) using leaf natural 13C abundance - Cornet, D.; Sierra, J.; Bonhomme, R. (2007)
A total of 23 genotypes belonging to seven tropical food yams and two wild relative species of different origin and coming from two sampling ecological zones (the Republic of Benin in Africa and Guadeloupe in the Caribbean) was analysed for their 13C content. The δ13C values for all yam samples (from –25.39 and –30.07 ‰) indicated that all species had a C3 photosynthetic type.